Sociology as a Serious Source of Anomaly in Thomas Kuhn's System of Science - Jacobs, Struan (Institutional Knowledge at Singapore Management University, 1997)
It is a testimony to the enduring importance of Thomas Kuhn's The Structure of Scientific Revolutions that, 30 years on, its doctrines of normal science and paradigm, incommensurability and revolution continue to challenge metascien tists and stimulate vigorous debate. Critique has mainly come from philosophers and historians; by and large, interested sociologists have embraced Kuhn. Un justifiably so, this article argues, bringing to light a serious difficulty or anom aly in his account of the social side of science. Contrary to what he claims, scientific knowledge is not the achievement of organic communities. It is con structed in trans-epistemic arenas by diverse participants, laypeople, and specialists. Accepting community is a flawed concept in the sociology of science, and in appreciating the major role Kuhn assigned it, the Kuhnian system looks less robust than it did before.